2012
DOI: 10.1371/journal.pone.0040711
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Dissection of Four Major QTL Affecting Milk Fat Content in the German Holstein-Friesian Population

Abstract: Milk composition traits exhibit a complex genetic architecture with a small number of major quantitative trait loci (QTL) explaining a large fraction of the genetic variation and numerous QTL with minor effects. In order to identify QTL for milk fat percentage (FP) in the German Holstein-Friesian (HF) population, a genome-wide association study (GWAS) was performed. The study population consisted of 2327 progeny-tested bulls. Genotypes were available for 44,280 SNPs. Phenotypes in the form of estimated breedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
75
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 36 publications
(55 reference statements)
19
75
1
3
Order By: Relevance
“…The polymorphisms of AGPAT6 were highly significantly associated with the milk fat percentage estimated breeding values in the German Holstein-Friesian population, as shown in a recent research (Wang et al, 2012). The result of a study by Nafikov (2010) showed that AGPAT6 was associated significantly with large differences in the compositions of milk fat, such as concentrations of saturated fatty acids, unsaturated fatty acids, monounsaturated fatty acids, and so on.…”
Section: Introductionmentioning
confidence: 66%
“…The polymorphisms of AGPAT6 were highly significantly associated with the milk fat percentage estimated breeding values in the German Holstein-Friesian population, as shown in a recent research (Wang et al, 2012). The result of a study by Nafikov (2010) showed that AGPAT6 was associated significantly with large differences in the compositions of milk fat, such as concentrations of saturated fatty acids, unsaturated fatty acids, monounsaturated fatty acids, and so on.…”
Section: Introductionmentioning
confidence: 66%
“…Significant associations involving markers within or close to other fat metabolism associated genes such as FASN, SREBPB1 and STAST5A have also been reported for milk production traits in dairy cattle [20]. In a recent study of a German Holstein-Friesian population, two highly significant polymorphisms were found to be associated with milk fat content; one of these variants is located within the promoter region of the EPS8 gene on chromosome 5 and the other variant is located near the GPAT4 gene on chromosome 27 [158].…”
Section: Candidate Genes Identified In the Key Tissues Through Associmentioning
confidence: 90%
“…Interaction of the EPS8 gene product with EGFR increases the signalling response to epidermal growth factor (EGF) [123]. The promoter SNP reported by [158] in EPS8 may mediate the binding of transcription factor TFAP2A to influence the transcription rate of EPS8. The expression of TFAP2A is correlated with the concentration of NEFA and liver triacylglycerol [158].…”
Section: Candidate Genes Identified In the Key Tissues Through Associmentioning
confidence: 99%
See 1 more Smart Citation
“…Conservative cattle genome regions with significant associations with milk production traits have been defined: casein cluster (CSN), diacylglycerol O-acyltransferase (DGAT1), growth hormone receptor (GHR) and others, as well as a number of not previously described population-wide mutations [20][21][22]. Studies of associations for low inheritable traits make it possible to improve breeding effectiveness by detection or elimination of genes responsible for the health and reproduction of animals, and to fix valuable genotypes in the population [23][24][25][26][27].…”
mentioning
confidence: 99%